2021
DOI: 10.13057/biodiv/d220154
|View full text |Cite
|
Sign up to set email alerts
|

Potential analysis of location, socio-culture and biodiversity as ecotourism attraction in Valentine Bay on Buano Island, West Seram, Maluku, Indonesia

Abstract: Abstract. Siahaya ME, Matius P, Aipassa MI, Rayadin Y, Ruslim Y, Aponno HSES. 2021. Potential analysis of location, socio-culture and biodiversity as ecotourism attraction in Valentine Bay on Buano Island, West Seram, Maluku, Indonesia. Biodiversitas 22: 438-448. This study aims to analyze the potential of flora and fauna in the mangrove ecosystem as an attraction for ecotourism development, knowing the role of stakeholders in supporting ecotourism development strategies in the mangrove area of Valentine Bay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Which are overgrown with pedadas (Sonneratia alba), because these animals eat the leaves/flowers and fruit of the pedada (Scylla spp), Crab (Polymesoda erosa), Lizard (Veranus salva) tor) and Snake (Fordonia leucobalia). This is in line with According to [29] and [30], mangrove ecosystems have diversity of mammals, reptiles, fish, and invertebrates so that it can be a special attraction for the development of mangrove ecosystem tourism in the area. [31] assesses that the results of the analysis carried out in the Pangempang Beach area have the potential for marine tourism with a background of mangrove forests, beaches and holding a coastal cultural festival featuring regional dances and tribes in Muara Badak District.…”
Section: Panrita Lopi Beach Managementsupporting
confidence: 62%
See 1 more Smart Citation
“…Which are overgrown with pedadas (Sonneratia alba), because these animals eat the leaves/flowers and fruit of the pedada (Scylla spp), Crab (Polymesoda erosa), Lizard (Veranus salva) tor) and Snake (Fordonia leucobalia). This is in line with According to [29] and [30], mangrove ecosystems have diversity of mammals, reptiles, fish, and invertebrates so that it can be a special attraction for the development of mangrove ecosystem tourism in the area. [31] assesses that the results of the analysis carried out in the Pangempang Beach area have the potential for marine tourism with a background of mangrove forests, beaches and holding a coastal cultural festival featuring regional dances and tribes in Muara Badak District.…”
Section: Panrita Lopi Beach Managementsupporting
confidence: 62%
“…Sustainability tools are essential for destination management. The ten main groupings of tools include area protection, industry regulation, visitor management techniques, environmental impact analysis, supporting capacity calculations, consultation and participation techniques, codes of conduct, sustainability indicators, carbon budget analysis and fair trade in tourism [37] and the tourism development strategy is to develop ecotourism, promote the attractiveness of ecotourism, develop educational tourism education, and promote diversity of flora, fauna, culture, and traditional customs [30].…”
Section: Management Of Sustainable Tourism Destinationsmentioning
confidence: 99%
“…There are 39 species of bird found in the protected forest area on Buano island include: nuri maluku (Eos bornea), nuri raja ambon (Alisterus amboinensis), kasturi tenguk ungu (Lorius domicella), kakatua seram (Cacatua moluccensis), nuri telinga biru (Eos semilarvata), kehicap buano (Symposiachrus boanensis), nuri pipi merah (Geoffroyus geoffroyi), uncal ambon (Macropygia amboinensis), raja perling seram (Basilornis corythaix), kepudang seram (Oriolus forsteni), isap madu seram (Lichmera monticola), cikukua seram (Philemon subcorniculatus), gagak hutan (Corvus enca), trinil semak (Tringa glareola), cekakak sungai (Todiramphus chloris), walet sapi (Collocalia esculenta), kuntul karang (Egretta sacra), cabak maling (Caprimulgus macrurus), delimukan zamrud (Chalcophaps indica), pergam laut (Ducula bicolor), pergam mata putih (Ducula perspicillata), tekukur biasa (Streptopelia chinensis), walik dada lembayung (Ptilinopus viridis), tiong lampu biasa (Eurystomus orientalis), bubut alang alang (Centropus bengalensis), wiwik maluku (Cacomantis aeruginosus), cabai kelabu (Dicaeum vulneratum), srigunting lencana (Dicrurus bracteatus), cikalang kecil (Fregata ariel), tepekong kumis (Hemiprocne mystacea), gosong forsten (Megapodius forsteni), kehicap pulau (Monarcha cinerascens), sikatan kelabu (Myiagra galeata), sikatan burik (Muscicapa griseisticta), betet kelapa paruh besar (Tanygnathus megalorynchos), kipasan dada lurik (Rhipidura rufiventris), celepuk Maluku (Otus magicus), perling ungu (Aplonis metallica). Siahaya et al (2021) stated that the number of birds identified on Buano Island was 28 species. This is due to the short time in conducting research so that the presence of the birds was not visible at that time.…”
Section: Potential Of Faunamentioning
confidence: 99%
“…The influence of mackerel is notably substantial in the production of diverse processed food items in Indonesia. Nonetheless, it's noteworthy that one mackerel species, Scomberomorus commerson, has been classified as "Near Threatened" according to the IUCN conservation status (Siahaya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%